1980
DOI: 10.1136/ard.39.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Plasma zinc and its relationship to clinical symptoms and drug treatment in rheumatoid arthritis.

Abstract: SUMMARY Total plasma zinc levels in patients with rheumatoid arthritis on different therapeutic treatments were determined in conjunction with total serum proteins, serum albumin and globulin, and articular index of joint tenderness, erythrocyte sedimentation rate, rheumatoid factor, serum copper, and serum iron. There were significantly lower zinc levels in patients with rheumatoid arthritis on nonsteroidal anti-inflammatory drugs than in patients on levamisole and penicillamine. Zinc levels correlated positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…The disease duration did not show correlation with the serum copper levels, even when the disease duration was considered related to the age of the patient, as in this study (Table 6), or when the duration of arthritis over 1 y was considered (Honkanen et al, 1989), or the mean of 8.6 y (Balogh et al, 1980). The number of inflamed joints, besides correlating positively with serum copper level (Table 6), was the only disease characteristic that showed statistical significance on the variation of this level (Table 7).…”
Section: Serum Coppermentioning
confidence: 52%
See 1 more Smart Citation
“…The disease duration did not show correlation with the serum copper levels, even when the disease duration was considered related to the age of the patient, as in this study (Table 6), or when the duration of arthritis over 1 y was considered (Honkanen et al, 1989), or the mean of 8.6 y (Balogh et al, 1980). The number of inflamed joints, besides correlating positively with serum copper level (Table 6), was the only disease characteristic that showed statistical significance on the variation of this level (Table 7).…”
Section: Serum Coppermentioning
confidence: 52%
“…Serum albumin, which is an important Zn-carrier, is decreased during inflammation, and presents positive correlation with the reduced zinc levels (Milanino et al, 1993;Maes et al, 1997). Therefore, zinc absorption and distribution seems to be disturbed in JRA (Honkanen et al, 1989), implying that its serum level is probably, one of the nonspecific features of inflammation (Balogh et al, 1980;Honkanen et al, 1991a).…”
Section: Serum Zincmentioning
confidence: 99%
“…This modification seems to be associated with an increase in hepatic zinc uptake [22,23], such as recently confirmed in the acute inflammatory carrageenan induced pleurisy of the rat [16]. Patients suffering from chronic rheumatic inflammatory diseases such as rheumatoid arthritis [25,26] and psoriatic arthritis [26] as well as animals with established adjuvant arthritis [13,14] were shown to have lower than normal plasma zinc levels. Oral zinc supplementation has demonstrated beneficial effects in some patients [27].…”
Section: Introductionmentioning
confidence: 91%
“…Antiarthritic drugs in their active forms are complexed with copper 35 . The hypercupreuria was also suggested to be the outcome of dyslipedemia 43 or inflammation, as the cytokines have been reported to enhance the release of Cu thioneins during the oxidative burst of polymorphonuclear cells 44 . As many studies have reported higher levels of copper in active RA, therefore copper has been suggested to be used as an additional biochemical biomarker for RA 45 .…”
Section: Discussion:-mentioning
confidence: 99%
“…However lower values of zinc in other studies may be due to pharmacological treatments or other effects which also need to be considered. Serum zinc levels have been shown to decrease during acute-phase response of inflammation and with treatment with NSAIDS 44 . Probably alterations in inflammation may have some role in the levels of essential minerals.…”
Section: Discussion:-mentioning
confidence: 99%